2015
DOI: 10.1093/jjco/hyv155
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, prospective assessment of moisturizer efficacy for the treatment of radiation dermatitis following radiotherapy after breast-conserving surgery

Abstract: ObjectiveThe effect of heparinoid moisturizer use after acute skin damage for patients receiving whole-breast radiotherapy after lumpectomy is understudied.MethodsA total of 30 patients were randomly assigned to receive heparinoid moisturizer (Group M), and 32 patients comprised the control group (Group C). Patients in Group M were instructed to apply heparinoid moisturizer from 2 weeks following whole-breast radiotherapy, and to continue to use the moisturizer until 3 months after completion of whole-breast r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Because clinical studies showed that topical heparinoid improved stratum corneum hydration in humans, we first assessed whether topical heparinoid‐containing product, Hirudoid ® cream, produces comparable benefits in mice. Indeed, twice‐daily applications of Hirudoid ® cream significantly elevated the levels of stratum corneum hydration, while neither baseline transepidermal water loss rates (TEWL) nor skin surface pH differed in Hirudoid ® cream‐treated versus Hirudoid ® cream‐untreated controls (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because clinical studies showed that topical heparinoid improved stratum corneum hydration in humans, we first assessed whether topical heparinoid‐containing product, Hirudoid ® cream, produces comparable benefits in mice. Indeed, twice‐daily applications of Hirudoid ® cream significantly elevated the levels of stratum corneum hydration, while neither baseline transepidermal water loss rates (TEWL) nor skin surface pH differed in Hirudoid ® cream‐treated versus Hirudoid ® cream‐untreated controls (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, topical heparinoid‐containing cream not only reduces postoperative ecchymosis and oedema, but also prevents the development of pressure ulcers . Furthermore, topical applications of a heparinoid‐containing product significantly increased stratum corneum hydration in both young and aged humans, as well as both epidermal growth factor receptor inhibitor‐ and radiotherapy‐induced skin dryness . Additionally, a questionnaire survey found that twice‐daily applications of a heparinoid cream or lotion for 1 month markedly improved skin dryness, pruritus and inflammation in subjects with atopic dermatitis, particularly in older patients .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the subjects did not use moisturizer until after radiodermatitis occurred. Sekiguchi et al reported that the application of a heparinoid moisturizer for 2 weeks resulted in lower skin dryness and desquamation compared to the non-application thereof (17). Therefore, medical staff should advice their patients regarding the appropriate timing of moisturizer usage.…”
Section: Duration Of Skin Observation and Self-carementioning
confidence: 99%
“…In our previous report, the application of heparinoid moisturizer for 2 weeks following whole-breast radiotherapy (WBRT) significantly increased skin water content (WC) and helped improve skin dryness and desquamation compared with no use of moisturizer ( 6 ). The aim of this study is to assess the efficacy of heparinoid moisturizer as a prophylactic agent for ARD in patients with breast cancer receiving WBRT.…”
Section: Introductionmentioning
confidence: 99%